Success attributions and more multidimensional extensions of the sexual attribution bias to failure attributions, social emotions, and the desire for social interactions - Agthe, Maria; Sporrle, Matthias (2008)
According to the recently discovered sexual attribution bias (SAB), young adults attribute the success of same-aged, same-sex attractive stimulus persons in a more derogative way than the success of less attractive same-sex persons, whereas this pattern is reversed for members of the opposite sex. Because this bias has so far only been investigated with respect to attributions in success scenarios, two studies examined its potential transferability to other psychological variables and settings: Study 1 (N = 419) demonstrated analogous biases for emotions and the desire for social interaction, and Study 2 (N = 509) revealed that the SAB can also be extended to failure scenarios. Success attributions and more: multidimensional extensions of the sexual attribution bias to failure attributions, social emotions, and the desire for social interaction.